2009
DOI: 10.1021/la902098a
|View full text |Cite
|
Sign up to set email alerts
|

Range of Applicability of the Wenzel and Cassie−Baxter Equations for Superhydrophobic Surfaces

Abstract: The Wenzel and Cassie-Baxter equations depending on the extent of liquid/solid interfacial contact area were generally used to estimate water contact angles on superhydrophobic surfaces. In this study, a simple method is proposed on the criterion to use the Wenzel and Cassie-Baxter equations to evaluate the contact angle results on superhydrophobic surfaces. In this method, the difference between the theoretical (geometric) and experimental contact angle-dependent Wenzel roughness parameter, Delta r(w), and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(201 citation statements)
references
References 48 publications
8
192
1
Order By: Relevance
“…However, the double rough effect of nanocrystal texturing of microspheres is more similar to the natural surface structuring of a lotus leaf which may be more accurately explained by the Cassie-Baxter model. 39 According to this model, the contact of a droplet with a hydrophobic architecture is the combination of its contact with the actual material and the air pockets surrounding this material, increasing the apparent contact angle. The effect of this superhydrophobic coating is shown in Figure 7c, where surface tension in the liquid forms near perfect spherical droplets of water which exhibited roll-off angles of just 2-3°.…”
Section: Resultsmentioning
confidence: 99%
“…However, the double rough effect of nanocrystal texturing of microspheres is more similar to the natural surface structuring of a lotus leaf which may be more accurately explained by the Cassie-Baxter model. 39 According to this model, the contact of a droplet with a hydrophobic architecture is the combination of its contact with the actual material and the air pockets surrounding this material, increasing the apparent contact angle. The effect of this superhydrophobic coating is shown in Figure 7c, where surface tension in the liquid forms near perfect spherical droplets of water which exhibited roll-off angles of just 2-3°.…”
Section: Resultsmentioning
confidence: 99%
“…13,14) Recently, some researchers have studied on the transition state where Cassie and Wenzel states are present simutaneously. 1,9,15) Studies of transition from Cassie state to Wenzel state have been carried out and some important factors, affecting the occurrence of transition, such as contact line density, energy barrier, and spacing factors have been discussed. [16][17][18][19] Moulinet and Bartolo studied the droplet equilibrium state deposited on hydrophobic rough surfaces by using the real-time 3D imaging technique for different droplet sizes.…”
Section: Introductionmentioning
confidence: 99%
“…20) Erbil and Cansoy estimated the droplet penetration between the pillars by suggesting the modified Cassie-Baxter equation based on the geometry of square and cylindrical pillar patterns. 9) Although a number of studies have reported some important physics behind droplet wetting behavior on hydrophobic surfaces on the basis of experiments and modeling, clear understanding of transition wetting phenomena showing penetration of liquid between pillars is required for designing and controlling hydrophobic surfaces effectively. This article reports the experimental study on transition wetting behavior of water droplet on microstructured hydrophobic surfaces manufactured by CNC machining process and self-replication way with hydrophobic polydimethylsiloxane(PDMS).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a depinned state with static CAM can be determined by noticing the departure of an experimentally recorded APCA from the Cassie contact angle. In the process of investigating reported CAMs in literature, for surfaces with θY > 90°, Erbil et al conducted a detailed mathematical analysis of the deviation of APCA from that predicted by Wenzel and Cassie equations 5,43,44 . APCAs for 28 different surfaces (with known θY and square pillar geometry) were listed and, using the Cassie equation, converted to a solid fraction term.…”
Section: Surface Design For Quasi-static Robustness: Pressure Balancementioning
confidence: 99%